Biały tydzień. (Gdańsk : [s.n.], 1954)
Afisz inf. o białym tygodniu w Powszechnych Domach Towarowych w 3mieście 27.09-3.10.1954 r.
Keywords: Handel -- Polska -- 1945-1970 -- druki ulotne; Sklepy -- Polska -- 1945-1970 -- druki ulotne; Gdańsk (Polska) -- 1945-1970 -- druki ulotne; Gdynia (Polska) -- 1945-1970 -- druki ulotne; Sopot (Polska) -- 1945-1970 -- druki ulotne